TRANSLATION OF COLOR IDIOMS FROM ENGLISH INTO UZBEK (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article gives information about types of idioms, the translation of color idioms from English into Uzbek, and what factors a translator should consider while translating. Additionally, some examples of color idioms are given with their definitions and alternatives in the target language